دور الإعفاءات الجبائية في تحفيز وترقية القطاعات الاقتصادية بالجزائر -دراسة إحصائية وقياسية للفترة الممتدة بين 2001 و 2021 باستخدام ARDL-: The role of tax exemptions in stimulating and promoting economic sectors in Algeria-A statistical and econometric study for the period extending between 2001 and 2021 using ARDL- - لجناف عبد الرزاق; يعقوب سلمى (Journal of North African Economies, 2025)
This study aims to know the role of fiscal incentives in increasing the volume of economic investments for various sectors through tax exemptions and incentives in accordance with the investment laws applied in Algeria since 1993 to the present day, through the establishment of various investment-supportive agencies directed towards investment projects in order to create positions Employment, new value surpluses, and then expanding the tax bases to increase the state's resources. The study concluded that the fiscal incentives policy in Algeria is insufficient in order to achieve the aforementioned goals. Because the investment climate in Algeria is not suitable for that, depending on econometric methods.